PASANG SURUT DAN FRAGMENTASI POLITIK ISLAM DI INDONESIA - Miftahussurur Miftahussurur (Jurnal Dialog, 2017)
This descriptiveanalytics article is aimed to traceback the dynamics and fragmentation of political Islam in Indonesia. It focuses on relation between the dynamics of political Islam and its historical process and its social-political context. After reformation era, the power of political Islam in Indonesia has been getting highly and more fragmented. Rather, the fragmentation was seemingly caused by interest of elites than ideology dispute. It was the reason why the power of political Islam has been never unified, even to boost the people’s interest. The political Islam tended to struggle enforcing God’s law (syariah) rather than solving the real problem such as economy and basic need of society or ummah. In the fact, enforcing the Syariah law was merely artificial one. Finally, the political Islam always fails in transforming social, economy and politics due to its elitism.